Tanning and beauty: Mother and teenage daughters in discussion. (July 2016) - Hay, Jennifer L; Geller, Alan C; Schoenhammer, Maria; Gordon, Mallorie; Bishop, Marilyn; Shuk, Elyse; Oliveria, Susan; Halpern, Allan C
Tanning increases dramatically through the teenage years, but the family context of this health risk behavior is relatively unstudied. We conducted videotaped conversations between teenage girls (10th and 11th grade) and their mothers. We developed a coding system for discussion content and highlight findings including inadequate knowledge concerning the harms of tanning and positive views of outdoor tanning over indoor tanning, yet agreement that all tans are attractive. Many teens believed that indoor tanning is sometimes necessary to achieve the tanned look. These findings can usefully guide intervention development regarding the harms of all tanning, rather than indoor or outdoor tanning specifically.